A Case Study of Strategic Planning for Perdana Cigna Insurance Berhad - Tang, Kwong Yin (1999)
The after effects of Asian Currency Crisis were still lingering in the economies of South East Asia countries. The crisis begun in July 1997, however, the general insurance industry took the brunt of the economic downturn in 1998. The 1997 financial result for general insurance companies shown good return and potential growth in gross and net written premium, and profit for the next financial year. Most general insurance companies including Perdana CIGNA Insurance Berhad h ad targeted major growth in 1998. The uncertain economic conditions dashed the company's hopes of producing the desired results. The general insurance market or premium size had shrunk considerable, especially, in motor insurance, as there are less new cars and devaluation of second hand car value. Other general insurance lines like fire was also affected as the value of properties were reduced, along with the fire insurance premium. The general insurance companies competed among each other to achieve growth and profitable, thus, reduction of premium occurred as too many insurers were fighting for business. Perdana CIGNA Insurance Berhad had a small portfolio of motor insurance, therefore, massive drop of turnover or net written premium did not occurred. However, losses i n claims were high and desirable growth was not achieved in 1998. Despite of the economic downturn, companies must reorganized and planned to take on new challenges or fight for survival as the most cost efficient and innovative company would be able to weather out the bad economic conditions.